DESCRIPTIVE STUDY OF INTEREST IN BECOME AN ENGINEERING TEACHER AMONG AUTOMOTIVE ENGINEERING EDUCATION STUDENTS - Rianto, Ravaldo Candrasukma (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
This study aims to explore the perceptions of Automotive Engineering Education students regarding the profession of automotive teachers and how these perceptions influence their interest in pursuing a career in this field. Vocational education, especially in automotive engineering, plays a crucial role in preparing the younger generation for the workforce. Students' interest in the automotive teacher profession is influenced by factors such as the challenges faced, career opportunities, and social recognition. This research uses a descriptive method with a quantitative approach. The research sample consists of 10 students from the 2023 cohort, selected using a simple random sampling technique. The results show that the majority of respondents (64%) are not interested in becoming a teacher, with the main reasons being low salary, high workload, and lack of recognition for the profession. However, 36% of respondents expressed interest in becoming teachers, citing reasons such as job stability, positive impact on society, and family encouragement. Most respondents (80%) are willing to become teachers if given the opportunity, although many feel that this profession lacks appreciation. The findings indicate the need for efforts to improve recognition of the automotive teacher profession and to develop strategies to attract more students to pursue a career as automotive teachers, in order to support the advancement of automotive engineering education in the future